A study on the suitability of the death penalty on women offenders in Malaysia / Jazmin Yaacob … [et al.] - Yacob, Jazmin; Musa, Nurul Hasinah; Shaheed Ali, Razinah; Wan Saadan, Wan Norsyedwiza (2009)
Picture in your mind a condemned murderer being sentenced to death, eating a last meal, or trudging ever-so-reluctantly into the execution chamber. You could have never imagined that this could be a woman.1 This study concerns the suitability of the death penalty on women offenders in Malaysia. The word 'suitability' originated from the word 'suitable' which can be defined as something that is right and appropriate for a particular purpose or occasion. In this study, we will look at the history of the death penalty, offenses which will result in the imposition of the capital punishment, feminist point of view on the death penalty imposed on women offenders, number of women offenders in our country facing the death row, existing legislation concerning women offenders, whether death penalty acts as a mechanism of deterrence for women offenders and whether other form of punishment could be introduced to replace the imposition of the controversial death penalty on women offenders.